Speech Acts Analysis Used in Jac Schaeffer’s Wandavision - Raflis Raflis; Niko Syahputra (Fakultas Sastra Universitas Ekasakti, 2022)
This research is pragmatic approach study an analysis of speech act used in Jac Schaeffer's Wandavision. The objectives of this researcher are to find out the types of illocutionary acts are performed by all the characters utterance, and to find out the types of illocutionary act dominantly used in Jac Schaeffer's wandavision. The researcher used descriptive-qualitative method to describe and analyze the selected of illocutionary acts which are watching movie and then classifies them according to George Yule’s and Yan Huang's concept types of illocutionary acts. Technique of collecting the data are (1) downloading the movie and movie script of Jac Schaffer’s Wandavision, (2) watching the movie while correcting the script based on the movie (3) taking notes which types of speech act were used in it (4) groups the speech act that occur based on Searle’s and Huang’s theory about speech act. The researcher used descriptive analysis which focus on classifying the types of illocutionary acts and the types of illocutionary acts used in Jac Schaeffer’s Wandavision carried out by all the character. The researcher found 165 speech acts in all episodes of the Wandavision series, namely 33 representative speech acts, 17 commissive speech acts, 79 directive speech acts , 3 declarative speech acts, and 33 expressive speech acts. The most dominantly used type of illocutionary act in Wandavision series is directive speech act consisting of 79 utterances with percentage of 47.88%.